Types of Commentaries in Lesia Ukrainka’s Translations of Ivan Franko’s Short Stories (Linguostylistic Studies, 2016)
The article focuses on rigorous comparative analysis of the original and translated by Lesia Ukrainka into Russian stories by I.Franko (the case study of 6 stories by Ivan Franko in their Russian translation). The analysis is aimed at clarification of the role and functions of translation comments as possible ways to compensate the semantic losses, inevitable in any translation, including such closely related languages as Ukrainian and Russian. The emphasis is laid on the varieties of translatem that need such commenting and on the detailed analysis of the translator's notes as a means to compensate the semantic loss of source language meaning. The efficiency of using translation commentaries outside a target text has been proved. The author claims that the majority of comments in translation can be classified into linguistic-cultural, linguistic proper and historical (background) types. They give additional information which can not be integrated into the translated text. Using translation strategy of commentaries gives the translator an opportunity to render the text into a target language practically without any significant semantic losses. Linguistic cross-cultural comments are typical for the translation of no-equivalent units of the original, among which the most numerous in terms of national semantics are historical and everyday realities, proper names, etiquette formulas that have the status of regional realities with an obligatory cultural component. Proper linguistic comments are applied when translating foreign words, jargons and slang words. Background (historical) commentary refers to certain facts of the past or contemporary socio-political or religious realities. The key findings of the case study of 6 stories by Ivan Franko in their Russian translation by Lesia Ukrainka provide grounds to conclude that the translator usually gives her comments in the form of footnotes, and some of the words are integrated into the text of translation itself, being enclosed in parentheses. Key words: Slavonic languages, literary translation, translation commentary, ethnocultural information, semantic loss compensation. References